Estimate of Some Immune-Biomarkers in Children with Entamoeba Histolytica Infection - Shakour, Sunbul Jalal (Journal of Medical Genetics and Clinical Biology, 2024)
The current work was aimed to evaluate of some immune-biomarkers in children with Entamoeba histolytica infection. General stool examination was done to patients for detection of E. histolytica infection. A total 150 patients of less than 13 years, whom attended the parasitology section at period February to June 2023. The chosen patients were suffered from abdominal pain and diarrhea. The results showed that gender is not related to infection with E. histolytica, as there were no significant (P≤0.05) differences between the proportions of males and females. The IgG concentration of infected children (24.05±3.94 ng/L) indicated a significant (P≤0.05) rise compared to the healthy children (11.72±2.55 ng/L). IgA concentration of infected children (159.42±18.62 ng/L) indicated a significant (P≤0.05) rise compared to the healthy children (38.93±7.01 ng/L). IgM concentration of infected children (4.84±0.45 ng/L) indicated a significant (P≤0.05) rise compared to the healthy children (2.17±0.35 ng/L). The IL-4 concentration of infected children (29.47±4.04 pg/ml) indicated a significant (P≤0.05) rise compared to the healthy children (16.54±3.94 pg/ml). IL-6 concentration of infected children (183.25±21.37 pg/ml) indicated a significant (P≤0.05) rise compared to the healthy children (26.12±4.51 pg/ml). The TLR2 levels of infected children (24.05±3.94 ng/L) indicated a significant (P≤0.05) rise compared to the healthy children (11.72±2.55 ng/L). therefore, its concluded that E. histolytica lead to a high immune response that leads to an increase in levels of immune parameters in infected children